The Miraculous Salvation of Constantinople from the Ottoman Siege in 1422 as Viewed by the Byzantines - Tatiana Viktorovna Kushch (Античная древность и средние века, 2019)
This article addresses the Ottoman siege ofConstantinoplein 1422, which ended with a fruitless assault on the city. Byzantine writers (John Kananos, Joseph Bryennios) described the miracle when the Mother of God appeared to go through the city walls during the assault. Contemporaries were convinced that the Mother of God, as a traditional defender and heavenly patroness ofConstantinople, helped to save the city. The author of this article have analyzed the account of miraculous deliverance of the capital from the Ottoman occupation, the besieged persons’ perception of the reasons for their victory, the psychological atmosphere in the city, and the defenders’ faith in heavenly intercession. The article focuses on the study of the Byzantines’ historical memory of these events. From the analysis of the account by Castilian traveller Pero Tafur, there are reasons to conclude that many years after the Byzantines still remembered the role played by the Mother of God for the victory over the Ottomans in 1422, and told the legend of this miracle to the foreigners who came to Constantinople. It has been admitted that Tafur’s retelling the story of the miracle of the appearance of the Mother of God mixed with another city legend related to the building of Hagia Sophia.